Kajian Makna Simbolik dalam Kembar Mayang pada Konteks Pernikahan Adat Jawa sebagai Pengayaan Bahan Ajar di Sekolah SD Negeri 106158 - Lia Pertiwi; Rosmawaty Harahap; Elly Prihasti Wuriyani; Imam Muhardinata (Universitas Indraprasta PGRI Jakarta, 2022)
Kembar Mayang is one of the elements in Javanese traditional ceremonies. The terminology of Kembar Mayang is in the form of coconut leaves (young coconut leaves) which are decorated with flowers and leaves in such a way on banana stems. This study aims to describe the values and symbolic meanings of the Kembar Mayang ransom tradition in the Javanese wedding ceremony procession. The Kembar Mayang ceremony is a tradition that has ancestral values and is given to both the bride and groom to start a new life. In the traditional Javanese wedding ceremony, it has a symbolic meaning. The symbolic meaning is based on the object, the process of making Kembar Mayang. This research applied a qualitative approach model with a description method, meaning in the form of words that were described. The stages of qualitative research carried out were problem identification, problem limitation, problem focus determination, research implementation, data processing and meaning, theory emergence, and research results reporting. The results of the study were obtained based on data collection techniques, namely observation, interviews and documentation. The research was held in February 2022 at SD Negeri 106158. This study found that Kembar Mayang were known in the form of leaves decorated with flowers, young coconut leaves, banana stems, ransom ceremony. These Kembar Mayang function as witnesses to events and symbolically witness the change in status from single to marital status. Kembar mayang can also be used for death ceremonies. Therefore, there are two terms of Kembar Mayang as a marriage ceremony, while gagar mayang as a death ceremony in Javanese traditional tradition.